2010
DOI: 10.1159/000273471
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Urethroplasty for Anterior Urethral Strictures: Buccal versus Lingual Mucosal Graft

Abstract: Aim: To compare the results of substitution urethroplasty and donor site morbidity between buccal mucosal graft (BMG) and lingual mucosal graft (LMG). Patients and Methods: Patients who underwent single-stage dorsal onlay free oral mucosal graft substitution urethroplasty by Barbagli’s technique between January 2004 and August 2008 were included in this study. Patients who underwent buccal (cheek, lip) mucosal graft urethroplasty were included in group I and those who underwent LMG urethroplasty (tongue) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
1
28
1
4
Order By: Relevance
“…In this series as well as in other comparative series [12][13][14] , there was no difference in success rate between BMG and LMG. Therefore, LMG appears to be a valuable alternative in case BMG is not possible (e.g.…”
Section: Discussionsupporting
confidence: 52%
“…In this series as well as in other comparative series [12][13][14] , there was no difference in success rate between BMG and LMG. Therefore, LMG appears to be a valuable alternative in case BMG is not possible (e.g.…”
Section: Discussionsupporting
confidence: 52%
“…LMG has been proposed as a successful alternative to BMG, with equivalent surgical outcomes and lower graft site mor-bidity. 10,11 Human and animal studies have proven that that uptake of LMG is equivalent to BMG. 14,15 We had chosen to evaluate the morbidity of the graft site in anterior urethral strictures (excluding pananterior Oral mucosa urethroplasty >10 cm), as we found that up to 5 cm (total 10 cm on both sides) of lingual graft could be harvested easily without any significant morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently BMG urethroplasty is the most common procedure, claimed to be a virtual gold standard for substitution urethroplasty . As a result of known graft site morbidities and instances where one might struggle to find a suitable buccal mucosa graft, there has been recent interest in alternatives, such as LMG, which is shown to have outcomes equivalent to BMG and less morbidity . The present study aimed to compare lingual graft morbidity and urethroplasty outcomes against dorsal onlay BMG urethroplasty, in a randomized prospective study.…”
Section: Introductionmentioning
confidence: 99%
“…However, buccal mucosa may not be suitable for treating long complicated urethral strictures because of limited material [18]. Lingual mucosal graft urethroplasty is a good substitute for buccal mucosal graft urethroplasty with equally good results of urethroplasty with lower donor-site morbidity [23,24,25,26]. However, it has the same shortcomings as buccal mucosal graft urethroplasty.…”
Section: Discussionmentioning
confidence: 99%